2017
DOI: 10.1002/prot.25342
|View full text |Cite
|
Sign up to set email alerts
|

Design of anti-thyroid drugs: Binding studies and structure determination of the complex of lactoperoxidase with 2-mercaptoimidazole at 2.30 Å resolution

Abstract: Lactoperoxidase (LPO) belongs to mammalian heme peroxidase superfamily, which also includes myeloperoxidase (MPO), eosinophil peroxidase (EPO), and thyroid peroxidase (TPO). LPO catalyzes the oxidation of a number of substrates including thiocyanate while TPO catalyzes the biosynthesis of thyroid hormones. LPO is also been shown to catalyze the biosynthesis of thyroid hormones indicating similar functional and structural properties. The binding studies showed that 2-mercaptoimidazole (MZY) bound to LPO with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…21b,c,58 An X-ray study of the 7bound LPO complex has shown that 7 inhibits the LPOcatalyzed reactions by coordinating to the Fe-center of the enzyme via the C�S moiety (Fe•••S = 2.580 Å) (Figure S43). 58 Thus, it will be interesting to investigate whether the inhibitory activities of these selones/thiones (1−9) follow a similar trend in the case of the LPO-catalyzed oxidation reaction of 2,2′azino-bis-3-ethyl-benthiazoline-6-sulfonic acid (ABTS), as they have shown in the case of the inhibition of copper-containing tyrosinase enzyme. However, among all thione derivatives (4− 9), we found that the imidazole-based thiones 4 and 7 showed better inhibition efficiency than their benzimidazole and naphthimidazole counterparts, with the highest inhibitory potency observed in the case of commercially available antithyroid drug methimazole (4) with an IC 50 value of 7.4 μM (Table 4).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…21b,c,58 An X-ray study of the 7bound LPO complex has shown that 7 inhibits the LPOcatalyzed reactions by coordinating to the Fe-center of the enzyme via the C�S moiety (Fe•••S = 2.580 Å) (Figure S43). 58 Thus, it will be interesting to investigate whether the inhibitory activities of these selones/thiones (1−9) follow a similar trend in the case of the LPO-catalyzed oxidation reaction of 2,2′azino-bis-3-ethyl-benthiazoline-6-sulfonic acid (ABTS), as they have shown in the case of the inhibition of copper-containing tyrosinase enzyme. However, among all thione derivatives (4− 9), we found that the imidazole-based thiones 4 and 7 showed better inhibition efficiency than their benzimidazole and naphthimidazole counterparts, with the highest inhibitory potency observed in the case of commercially available antithyroid drug methimazole (4) with an IC 50 value of 7.4 μM (Table 4).…”
Section: Resultsmentioning
confidence: 95%
“…Imidazole-based thiones 4 and 7 and selone 1 are known to inhibit iron-containing metalloenzyme lactoperoxidase (LPO)-catalyzed oxidation reactions, which belong to the mammalian heme peroxidase superfamily. ,, An X-ray study of the 7 -bound LPO complex has shown that 7 inhibits the LPO-catalyzed reactions by coordinating to the Fe-center of the enzyme via the CS moiety (Fe···S = 2.580 Å) (Figure S43). Thus, it will be interesting to investigate whether the inhibitory activities of these selones/thiones ( 1 – 9 ) follow a similar trend in the case of the LPO-catalyzed oxidation reaction of 2,2′-azino-bis-3-ethyl-benthiazoline-6-sulfonic acid (ABTS), as they have shown in the case of the inhibition of copper-containing tyrosinase enzyme. However, among all thione derivatives ( 4 – 9 ), we found that the imidazole-based thiones 4 and 7 showed better inhibition efficiency than their benzimidazole and naphthimidazole counterparts, with the highest inhibitory potency observed in the case of commercially available antithyroid drug methimazole ( 4 ) with an IC 50 value of 7.4 μM (Table ).…”
Section: Resultsmentioning
confidence: 99%